Slovene national minorities and emigrants in grammar school geography and history syllabi - Javornik Krečič, Marija (Studia Historica Slovenica, 2016)
Content related to national minorities and emigrants has a high educational potential, which manifests itself in the following ways: through learning about national historical developments, their causes and consequences; through learning about geographical areas where Slovenes live, their special physical and socio-geographical features or their special spatial features; through recognizing, learning about and developing a (national and personal) identity and national awareness. After all, the personal stories of emigrants and members of national minorities are often rich in real-life experience that can be beneficial for a range of developing students. For this reason, Slovene national minorities and emigrants deserve a place in the curriculum of the Republic of Slovenia. The present article is based on a study of basic learning materials, i.e., syllabi, for comprehensive grammar schools in Slovenia. More specifically, it focuses on the position of national minorities and emigrants in the geography and history syllabi. The study is based on the descriptive method and on a comparative analysis of the two syllabi. It partly answers the question of how the program of comprehensive grammar schools influences knowledge about and attitude towards Slovenes abroad.
Keywords: gimnazije; kurikulum; narodne manjšine; Slovenija; slovenski izseljenci; učni programi